Various Doping Concentration Effect on Silicon-on-Insulator (SOI) Phase Modulator - Mardiana, Bidin; Haroon, Hazura; Hanim, Abdul Razak; Sahbudin, Saari; Abdullah, H. (2010)
This paper reports the effect of doping concentration to the electrical characteristic performance of the phase modulator in the carrier injection mode at wavelength 1.55μm. The phase modulator device has been integrated in the silicon-on-insulator (SOI) rib waveguide with the p-i-n diode structure. The electrical device performance is predicted using the 2-D semiconductor package SILVACO (CAD) software under DC operation. The least doping concentration of p+ and n+ region produces the least change of refractive index of the modulator. Meanwhile, results show that by increasing the doping concentrations, the value of I decreases. This means that the phase modulator performance is better with increased doping concentrations.